Anemia Hemolitik Autoimun Berat Pasca-vaksinasi mRNA COVID-19 - Randhy Fazralimanda (PT Kalbe Farma Tbk., 2023)
Vaccination have an important role in COVID-19 management, however clinicians should monitor its adverse effects. A young female was admitted to the emergency room with a severe anemia, shortness of breath and profound jaundice which was then diagnosed as autoimmune hemolytic anemia. Three days prior to the admission, she had her first dose of mRNA-based COVID-19 vaccine. After steroid administration and erythrocyte transfusion, her condition was better and her hemoglobin level was back to normal. An autoimmune condition triggered by vaccination should be closely monitored.